Gender, letters, relatives, and God: mediating actors in mammographic screening among Pakistani women in Norway. (September 2019) - Bhargava, Sameer; Hofvind, Solveig; Moen, Kåre
Background: Pakistani immigrant women in Norway have lower attendance rates in the national breast cancer screening program (BreastScreen Norway) compared to non-immigrants and immigrants from most other countries. Purpose: To identify and explore human and non-human actors that play a role for Pakistani immigrant women's attendance in the program. Material and Methods: Qualitative interviews with 16 Norwegian-Pakistani women in 2017 and 2018. Inspired by Latour, we explored how human and non-human actors act and interact when Pakistani immigrant women consider attendance in BreastScreen Norway. Results: Among the actors found to play a significant role in the relationship between Pakistani immigrant women and the screening program were trust in the healthcare system and breast cancer screening, the gender of the screening radiographer, the written information received from the screening program, family life, daughters, general practitioners, non-governmental organizations, religious beliefs, private service providers, monetary expenses, accessibility, worries, and digital tools. Conclusion: Many human and non-human actors work to shape and influence Pakistani immigrant women's screening attendance, or lack thereof, for instance by creating thoughts, promoting opportunities, raising doubts and generating worries, thus variously encouraging, enabling, facilitating, discouraging or preventing attendance in organized breast cancer screening.